EVALUASI PELAKSANAAN PERATURAN DAERAH NO. 3 TAHUN 2002 TENTANG HIBURAN UMUM (STUDI KASUS HIBURAN TAMAN PANCING) DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Putri Anggraini; Nurman Nurman (UIR Press, 2018)
This study aims to find out the Evaluation of the Implementation of Local Regulation no. 3 Year 2002 About Public Entertainment (Case Study of Fishing Garden Entertainment) In Sub Marpoyan Damai Pekanbaru City. Assessment indicators Evaluation used includes Operating Permit, Operating Time, HO Permission License, Fines, Sanctions, and Criminal Provisions. The type of research located in Taman Pancing Entertainment Marpoyan Damai Subdistrict Pekanbaru City is a descriptive quantitative method, that is by using a method used to find the knowledge of the subject of research at a certain moment to express empirical facts objectively based on scientific logic. There are 4 population groups and the sample in this research is 1 Head of Tourism and Development of Tourism Industry, 3 business owners, 15 visitors of Taman Pancing Park and 6 People of Public. The sample size assigned from these four groups is 25 people. Two sampling techniques used in determining individual samples are saturated sampling techniques for the Group of Business Owners and Head of Tourism Development and Industrial Development and purposive sampling techniques for Visitor and Community Figure groups. Types and data collection techniques used consisted of primary data collected using questionnaire and interview techniques and secondary data collected using observation and documentation techniques. While the data analysis technique used is to classify data based on the type and form of data then the results of the data presented in the form of tables and descriptions are then described descriptively. Based on this analytical technique, the researcher evaluates and concludes that the evaluation of the implementation of regional regulation no. 3 Year 2002 About Public Entertainment (Case Study of Fishing Garden Entertainment) In Sub Marpoyan Damai Pekanbaru City is at the interval of Appraisal Good.